2017
DOI: 10.1038/s41598-017-01000-2
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of responsiveness to immune checkpoint inhibitors

Abstract: Modulation of the immune system can produce anti-tumor responses in various cancer types, including melanoma. Recently, immune checkpoint inhibitors (ICI), in single agent and combination regimens, have produced durable and long-lasting clinical responses in a subset of metastatic melanoma patients. These monoclonal antibodies, developed against CTLA-4 and PD-1, block immune-inhibitory receptors on activated T-cells, amplifying the immune response. However, even when using anti-CTLA-4 and anti-PD-1 in combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 48 publications
2
70
1
Order By: Relevance
“…That ECM composition and remodeling play a key role in mediating response to ICBs is also confirmed by the signatures of resistance to ICBs that evidence the up-regulation of ECM components or factors that contribute to ECM remodeling [19][20][21].…”
Section: Ecm and Hypoxiamentioning
confidence: 69%
See 3 more Smart Citations
“…That ECM composition and remodeling play a key role in mediating response to ICBs is also confirmed by the signatures of resistance to ICBs that evidence the up-regulation of ECM components or factors that contribute to ECM remodeling [19][20][21].…”
Section: Ecm and Hypoxiamentioning
confidence: 69%
“…The proteomic analysis of formalin-fixed, paraffin-embedded metastatic melanoma tissues collected prior ICBs evidenced 106 significantly different proteins between responding and non-responding groups [19]. The analysis showed that non-responding tumors were characterized by elevated histone H3 lysine [27] trimethylation (H3K27me3) and decreased E-cadherin, features related to a more mesenchymal phenotype.…”
Section: Cancer Emt Signatures and Resistance To Icbsmentioning
confidence: 99%
See 2 more Smart Citations
“…7E and F). CCL2 expression was correlated with CD3ā€positive, CD8ā€positive Tā€cell infiltration in several studies . CCL2, CXCL5, CXCL8, and CXCL12 are suggested to play a role in monocyte recruitment in the tumor microenvironment, and CCL28 is involved in regulatory T cell recruitment that may be associated with the promotion of immune evasion.…”
Section: Discussionmentioning
confidence: 95%